Prevalence of angular leaf spot disease and sources of resistance in common bean in eastern democratic republic of Congo - Kijana, R.; Abang, Mathew M.; Edema, Richard; Mukankusi, Clare Mugisha; Buruchara, Robin Arani (African Crop Science Society, 2017)
Angular leaf spot (Pseudocercospora griseola Crous U, Brown) is one of the most important diseases hindering common bean (Phaseolus vulgaris L.) production in the Great Lakes Region of Africa, including the Democratic Republic of Congo. The disease causes extreme yield losses, estimated at 384.2 tonnes per year, in Sub-Saharan Africa. Little is known about the distribution, severity and incidence of the disease and the effect of agronomic practices and environmental factors on the disease prevalence in the country to facilitate interventions. A field survey was conducted during two crop seasons, February to June and September to January, in two main beans growing zones of eastern DRC namely; sub-humid highland and sub-humid mid altitude at low latitudes, in South and North Kivu, respectively. Severity and incidence of angular leaf-spot and other occurring diseases were assessed on common bean plants in farmers’ fields. Angular leaf spot in these fields had an average severity index (PSI) of 49.9%. PSI was significantly different (P<0.05) between districts and seasons. Using multiple regression analysis, independent variables: growth stage, cropping system, districts and altitude were shown to have significant influence on the observed PSI (P<0.05) with R2 = 96.2%. The highest severity (PSI=59.7%) was observed in Kabare district, and the lowest in Uvira district (PSI=39.5%). Screening of a set of 37 released common bean varieties in DRC using virulent Andean and Mesoamerican isolates identified four resistant bean varieties; ARA 4, COD MLV 059, MLV 224/94B, LSA 144 and Mexico 54. Some of these varieties possess useful traits, in addition to acceptable seed market class, and are hence recommended as suitable parents for ALS resistant variety development and promotion in ALS prone environments.